Dissemination of clinical Escherichia coli harboring the mcr-1 gene in Pakistan - Abdullah, Sabahat; Mushtaq, Muhammad Ahmad; Ullah, Kalim; Hassan, Brekhna; Azam, Mariya; Zahoor, Muhammad Asif; Wang, Juan; Xu, Jianzhen; Toleman, Mark A.; Mohsin, Mashkoor (Frontiers in Microbiology, 2025)
BackgroundColistin is an antibiotic used as a last resort to treat multidrug-resistant Gram-negative bacterial infections. Plasmid-mediated mobile colistin-resistant (mcr) genes in Escherichia coli (E. coli) are disseminated globally and are considered to be a major public health threat. This study aimed to determine the molecular characteristics of colistin-resistant Escherichia coli isolates in clinical settings in Pakistan.MethodsA total of 240 clinical E. coli strains isolated from urine and pus cultures were collected from two hospitals in Faisalabad and analyzed for phenotypic resistance to colistin by cultivation on CHROMagar plates supplemented with colistin 2 ug/ml. Molecular characteristics of colistin-resistant isolates were analyzed using conventional PCR, whole genome sequencing, and bioinformatics analysis.ResultsPCR and whole genome analysis confirmed the presence of the mcr-1 gene in 10 E. coli isolates. The minimum inhibitory concentration for colistin ranged from 4 ug/ml to 32 ug/ml. ResFinder analysis revealed the presence of multiple resistance determinants conferring co-resistance to β-lactams, aminoglycosides, trimethoprim, sulfonamides, tetracycline, quinolones, florfenicol, and macrolides. Hybrid genomic assembly indicated that mcr-1 is carried on IncI2 plasmids. Plasmid replicon typing indicated that IncI2-type plasmids (n = 10) were the most prevalent plasmids in these strains, followed by IncFIB (n = 8), IncFIC (n = 7), IncFIA (n = 6), IncFII (4), IncQ1 (n = 3), IncI1 (n = 1), IncY (n = 1), and IncN (n = 1). The Achtman MLST typing scheme revealed a large diversity of STs among the mcr-1-positive E. coli. VirulenceFinder analysis revealed the presence of numerous virulence factors ranging from 4 to 19.ConclusionOur study revealed the emergence and dissemination of colistin-resistant E. coli isolates carrying mcr-1 in hospital settings, posing a potential risk to anti-infective therapy. More efforts should be taken to monitor the prevalence of mcr-1-carrying bacteria in Pakistan.